The Effectiveness of the Contradictory Duals in Osama bin Munqith's Poetry - Jalout, Rawda Ibrahim (Journal of Humanities & Social Sciences, 2021)
Antagonistic dualities are a philosophical phenomenon that has been transferred to the context of literary criticism and then applied to literature, and it is a reflection of the aspects of the universe based on contradiction such as good and evil, light and darkness, existence and nothingness, death and life, and an expression of the human soul with its struggles and fluctuations, a term defined by our rhetorical inheritance. Among them are antithetical, equivalent equivalence, and considering literature as a form of self-expression, this research came to show the importance of oppositional dualities and the effectiveness of their presence in the literary text with the vitality they give it, in addition to their role in persuasion and influence through the element of paradox and astonishment that it creates in the recipient through the encounter of dualities And the collection of contradictory meanings, which are integrated in the service of the literary text , finding the pleasure of reading and receiving , working on analysis and creating semantics.
Keywords: Antonyms; Opposites; Single words; Structures; Pictures